2021
DOI: 10.1183/13993003.02990-2020
|View full text |Cite
|
Sign up to set email alerts
|

European Respiratory Society guidelines for the management of children and adolescents with bronchiectasis

Abstract: There is increasing awareness of bronchiectasis in children and adolescents, a chronic pulmonary disorder associated with poor quality-of-life for the child/adolescent and their parents, recurrent exacerbations and costs to the family and health systems. Optimal treatment improves clinical outcomes. Several national guidelines exist, but there are no international guidelines.The European Respiratory Society (ERS) Task Force for the management of paediatric bronchiectasis sought to identify evidence-based manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
212
1
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(263 citation statements)
references
References 124 publications
1
212
1
10
Order By: Relevance
“…using high‐resolution computed tomography (HRCT) and better understanding of the underlying pathomechanisms, the vicious circle of infection, neutrophilic inflammation, impaired mucociliary clearance and airway wall destruction may be interrupted, existing changes reversed and irreversible changes prevented. It is therefore essential to promptly start a diagnostic process if chronic suppurative lung disease and bronchiectasis are suspected in a child or adolescent to identify treatable factors and start treatment as soon as possible (1). A likely precursor of pediatric BE is protracted bacterial bronchitis (PBB) which is defined as chronic productive cough which resolves with two weeks of appropriate antibiotic treatment.…”
Section: Chronic Acquired and Genetic Lung Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…using high‐resolution computed tomography (HRCT) and better understanding of the underlying pathomechanisms, the vicious circle of infection, neutrophilic inflammation, impaired mucociliary clearance and airway wall destruction may be interrupted, existing changes reversed and irreversible changes prevented. It is therefore essential to promptly start a diagnostic process if chronic suppurative lung disease and bronchiectasis are suspected in a child or adolescent to identify treatable factors and start treatment as soon as possible (1). A likely precursor of pediatric BE is protracted bacterial bronchitis (PBB) which is defined as chronic productive cough which resolves with two weeks of appropriate antibiotic treatment.…”
Section: Chronic Acquired and Genetic Lung Diseasementioning
confidence: 99%
“…(2)). General treatment recommendations for pediatric BE include regular application of airway clearance techniques, antibiotic treatment for exacerbations and consideration of long‐term macrolide treatment in those with frequent exacerbations (1).…”
Section: Chronic Acquired and Genetic Lung Diseasementioning
confidence: 99%
“…A lot of work still needs to be done, as is shown by recent data from a European audit that found that while approximately 45% of almost 5,800 patients with bronchiectasis performed ACT, adherence was low. 39 Until now ACTs have been strongly recommended by experts, but there is still a low level of evidence both in adults and children, 40 possibly due to the wide variety of techniques applied in the studies and also the diversity of outcomes studied in the articles.…”
Section: Airway Clearance Techniquesmentioning
confidence: 99%
“…Important biological differences include altered pathogen profiles (bacteria [ 8 ] and microbiota [ 9 ]), age-related immunological responses [ 10 ] and treatment outcomes [ 1 ]. Diagnostic [ 1 ] and treatment methods, such as airway clearance techniques (ACTs), may also differ according to age [ 11 , 12 ]. Additionally, comorbidities and underlying aetiologies are substantially different between adults and children [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address the lack of published research priorities and patient-derived “needs assessment” data for CYP with bronchiectasis, we undertook this project as an extension of the European Respiratory Society (ERS) clinical practice guideline (CPG) for managing children and adolescents with bronchiectasis [ 12 ]. We sought to develop a roadmap to guide health services and research priorities pertinent to the needs of CYP (and their parents/carers) with bronchiectasis, in order to reduce their disease burden and improve their short- and long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%